Players Don’t Die, They Respawn: a Situational Analysis of Toxic Encounters Arising from Death Events in League of Legends - Nexø, Louise Anker (European journal on criminal policy and research, 2023)
Online death events constitute integral parts of many competitive online multiplayer games. Nonetheless, research has identified death events as frequently involved in the proceedings of toxic behaviors (Märtens et al., 2015). While much existing research has been attentive towards providing a range of explanations for the emergence of toxic behaviors in online games (see for example Kordyaka et al. in Internet Research, 30(4), 1081-1102, 2020; Kou, 2020; Kowert in Frontiers in Psychology, 11, 2020), research exploring the micro sociological mechanisms involved is currently limited. By applying a micro sociological situational approach to a sample of screen-recorded video data from an observational study of online toxic behaviors in League of Legends, we find that patterns of interactional rituals and situational properties play an important role in whether a death event, in which one or more players are killed, escalates into a toxic encounter. These preliminary results suggest a micro-situational understanding to be explored and refined in future empirical research. From the preliminary findings, a range of potential interventions to mitigate toxic behavior and promote social inclusion in online gaming are suggested. Among these, two types of social-norm interventions, targeting social referents and weakening social norms, align well with the main findings.